Harvesting Energy Saving Through Energy Audit : A Case Study of Local Government Building in Jakarta - Fahlevi, Oktasio; Simarmata, Todo Hotma T; Hadiyanto, Didik (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2024)
Electrical energy is a very important requirement to support regional government office activities. Excessive energy use can certainly cause energy waste, so to prevent excessive energy use it is necessary to take energy efficiency measurement. Energy Audit is the one method to measure how efficient the energy usage. Based on SNI ISO 50002 : 2018 regarding energy audit guidance, We conduct the energy audit at the one of local government building in Jakarta City. In doing so, the scope and objective of this energy audit project are to review and evaluate the energy consumption 3 years ago particular for electric, cooling and lighting system saving opportunities. The result from this project are the Enpi's value are 184 kWh/m2 per year. it can be indicated that the building inefficient in energy usage. The Power Quality Analyzer showing inefficient from electrical system because the cosh phi value is 0,75 and automatically get the penalty from PLN. The lighting system still in non LED technology. The Cooling system need improvement to make the energy consumption more efficient. There is a Solar pV rooftop potential installation that could give the contribution in energy saving around 134.963 kWh/Year. All of summary and recommendation that can be proposed in energy saving potential is 244.169 kWh/Year or 53% cost energy saving from existing cost energy consumption.